Слов'янська культура як основа становлення традицій української державності - Рязанов, Михайло Юрійович (My University, 2010)
Данная статья раскрывает зачатки украинской политической мысли как неотъемлемой составляющей национального интеллектуального достояния. Рассматриваются предпосылки развития общественно-политических идей, сформулированных выдающимися учеными, этапы развития государственности на украинской земле.

This article reveals seeds of Ukrainian political thought as an integral part of the national intellectual treasure. Considered prerequisites for the development of social-political ideas formulated by prominent scientists, stages of development of Ukrainian statehood. Analyze the contribution to development of democratic ideas of formation and operation of East Slavic states by B. Khmelnitskiy, M. Kostomarov, M. Dragomanov and other prominent ﬁ gures.
Keywords: слов'янська культура; становлення традицій; українська державність; політична думка; славянская культура; становление традиций; украинская государственность; политическая мысль; Slavic culture; formation of traditions; Ukrainian statehood; political Thought